If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-11+x=-8(-x+1)
We move all terms to the left:
-11+x-(-8(-x+1))=0
We add all the numbers together, and all the variables
x-(-8(-1x+1))-11=0
We calculate terms in parentheses: -(-8(-1x+1)), so:We get rid of parentheses
-8(-1x+1)
We multiply parentheses
8x-8
Back to the equation:
-(8x-8)
x-8x+8-11=0
We add all the numbers together, and all the variables
-7x-3=0
We move all terms containing x to the left, all other terms to the right
-7x=3
x=3/-7
x=-3/7
| 2/3*x+1/3=-5/9 | | |4x-5|+9=0 | | 0.1(50K)=x | | 5x=4x+160 | | 3(4x+3)=10x+19 | | 4=k/22 | | (25x+1)+(127x-1)=90 | | 20-0.1x=0 | | 10=4-v | | (25x+1)+(127x-1)=180 | | 0.3=0.6y | | 5×x=4x+160 | | 2/3x+1/3=-5/9 | | y=200+3 | | 12+4yy=5 | | x-90=4 | | -15=-4y+5* | | y=512+4y | | 7=v/16 | | 8x-2x+x=6 | | 16=2(x+1)=x | | -1.3+y=16.7 | | e/7-2.1=7.9 | | 8x-2x+2x=6 | | v=112 | | 3k−2k=7 | | 44+45l=179 | | 122=5n+7 | | 1+r=6 | | (x)=2x2+32 | | s+10/6=4 | | 18+3k=22+8k |